Stem Cells and Cancer Stem Cells, Volume 1 Stem Cells and Cancer Stem Cells, Therapeutic Applications in Disease and Injury: Volume 1 - Hayat, M.A.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
Difference between tissue specific stem cells and embryonic stem cells is explained. The advantages of the latter are included. The application of human pluripotent stem cells, mesenchymal stem cells, and hematopoietic stem cells in cancer therapy and tissue/organ regeneration is detailed. Role of neural cancer stem cells in brain tumors, including their role in brain tumor therapy and the role of CD133 stem cell antigen in glioma patients, is emphasized. Therapeutic role of bone marrow-derived stem cells in myocardial infarction and the role of mesenchymal stem cells in orthopedics are explained. Transplantation of umbilical cord hematopoietic stem cells and allogeneic hematopoietic stem cell transplantation followed by graft-versus-host disease are presented. Role of cancer stem cells specifically in glioblastoma and medulloblastoma is included. It is also emphasized that CD133 is an appropriate stem cell marker for gliomas. Targeting of cancer cells is also explained.
Keywords: Medicine; Oncology; Radiology, Medical; Neurosurgery; Pathology; Transplantation of organs, tissues, etc; Biomedicine; Cancer Research; Neuroradiology; Neurosurgery; Oncology; Pathology; Transplant Surgery